2020
DOI: 10.1002/cam4.3559
|View full text |Cite
|
Sign up to set email alerts
|

Higher miR‐543 levels correlate with lower STK31 expression and longer pancreatic cancer survival

Abstract: Pancreatic cancer (PC) is one of the most malignant gastrointestinal tumors worldwide, with more than 56,770 estimated newly diagnosed cases per year in United States in 2019. 1 As the most frequent cause of cancer deaths, PC is an extremely lethal disease with 45,750 cancer deaths annually. For all stages combined, PC has the worst prognosis with the lowest 5-year

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…To further explore the function of microRNA-543, we used published bioinformatics articles and online software prediction and found that microRNA-543 acts by targeting STK31 ( 22 ). In our study, we further verified the relationship between microRNA-543 and STK31.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further explore the function of microRNA-543, we used published bioinformatics articles and online software prediction and found that microRNA-543 acts by targeting STK31 ( 22 ). In our study, we further verified the relationship between microRNA-543 and STK31.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al showed that LncRNA PVT1 controls TRPS1 transcription in breast cancer by absorbing microRNA-543 ( 27 ). Yuan et al found that microRNA-543 was associated with the occurrence and prognosis of PC by targeting STK31 through a comprehensive bioinformatics analysis ( 22 ). However, they did not perform a thorough study, while we performed a deep study of the mechanism of this result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the function of microRNA-543, basing on the published bioinformatics article, we got that microRNA-543 worked by targeting STK31 [21]. In our study, we further veri ed the relationship between microRNA-543 and STK31.…”
Section: Microrna-543 Control Pc Development By Targeting Stk31mentioning
confidence: 64%
“…Further, previous research had reported that microRNA-543 plays a role in PC by targeting STK31 [21]. Then, we selected STK31 as a target gene of microRNA-543 for further research.…”
Section: Bioinformatics Analysismentioning
confidence: 98%